RANCANG BANGUN WEBSITE INTERAKTIF UNTUK MENYAJIKAN 10 WISATA TERPOPULER DI MAJALENGKA DALAM UPAYA MENARIK PENGUNJUNG - YULIANI PRATIWI; II SOPIANDI (Universitas Majalengka, 2025)
Majalengka is one of the regencies in West Java that possesses significant natural and cultural tourism potential, yet many people are still unfamiliar with its destinations. Therefore, an interactive and accessible promotional medium is required to increase public awareness. This study aims to design and develop an interactive website that presents information about the 10 most popular tourist attractions in Majalengka. The development method applied is the Rational Unified Process (RUP), consisting of the Inception, Elaboration, Construction, and Transition phases. The website was developed using the Laravel framework with MySQL as the database, and tested using the black-box testing method to ensure system functionality. The results show that the website can comprehensively present tourism information through features such as location maps, photo galleries, articles, and interactive comment sections. This website is expected to assist the local government in promoting tourism, provide greater exposure for tourism managers, and help tourists plan their visits more effectively.